Determinants of user innovator behavior in the silver market - Konstantin Wellner; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2014)
The existing research on the behavior of user innovators has focused almost exclusively on younger users. In light of the demographic shift and the increasing importance of the Silver Market segment (customers 55 years plus), we analyzed whether important determinants of user innovator behavior (use experience, product knowledge, technical expertise, and the lead user components) exert the same influence among older users. We conducted a study in the camping and caravanning industry and included 333 respondents from 19 to 86 years of age. The innovator share among older users was slightly lower (43 % vs. 57 %). While use experience and product knowledge turned out less important for older users in our sample, technical expertise materialized as the most important determinant. Additionally, being ahead of trend is stronger related to dissatisfaction with existing products among older users. We found additional evidence that users with high use experience suffer from functional fixedness.
Keywords: 330; user innovation; lead user; Silver Market; age; use experience; technical expertise; product knowledge; determinants